Faktor-Faktor Yang Mempengaruhi Permintaan Tanaman Hias di Desa Bangun Sari Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Dirgantari Putri; Khairul Saleh; Rahma Sari Siregar (Universitas Medan Area, 2021)
The purpose of this study was to determine what factors influenced the demand for ornamental plants in Bangun Sari Village. The sample in this study is the ornamental plants in Bangun Sari Village. The population of crop farmers consists of 315 farmers. Samples taken as much as 10% of the total population of 32 farmers. Then the sample taken in this study is consumers from32 ornamental plat farmers who are buying at the study site, determined purposively, namely 1 consumer from sample farmers. Based on the Uji F results simultaneously the price of ornamental plants, income and tastes significantly influence the demand for ornamental plants in Bangun Sari Village. Based on the results of the Uji t that partially the price of ornamental plats and consumer tastes significantly influence the demand for ornamental plants and income don’t significantly influence the demand for ornamental plants in Bangun Sari Village, Tanjung Morawa District, Deli Serdang Regency.